Pengaruh Pendidikan Bilingual terhadap Perkembangan Diksi, Tata Bahasa, dan Pelafalan Ujaran Bahasa Daerah Siswa - Hidayati, Amalia Safitri; Rusmawati, Roosi; Junining, Esti (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
In the era of globalization, bilingual education (Indonesian-English) which is encouraged in several schools has reduced the intensity of using local languages as mother tongue. This resulted in regional languages being at a critical level. Therefore, this study aims to describe the influence of bilingual education on the development of diction, grammar, and regional language pronunciation of bilingual education students. The method used in this study is a qualitative conversational method. The instruments in this study were researchers assisted by observation sheets. The results of the study state that at the diction level, code mixing occurs in regional languages, Indonesian, and English. At the grammatical level, sentences in Javanese, Indonesian and English are interchanged. On the other hand, at the pronunciation level, students experience problems learning phonemes in regional languages in the form of phoneme substitutions and silences. The factors that cause this to happen are the familiarity between speakers, the high intensity of the use of Indonesian and English, as well as the mastery of regional languages that are still limited.